2016
DOI: 10.1097/mnm.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Normal distribution pattern and physiological variants of 68Ga-PSMA-11 PET/CT imaging

Abstract: This study shows normal distribution pattern, range of SUVs, and physiological variants of Ga-PSMA-11. In addition, several potential pitfalls were documented to prevent misinterpretations of the scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 21 publications
7
95
1
4
Order By: Relevance
“…No cancer cells except one case of PDTC were immunoreactive for PSMA. No normal thyroid epithelium or non-neoplastic microvasculature were PSMA-positive, which is in the line with the recent biodistribution study that found minimal uptake of 68 Ga-PSMA-11 PET/CT radiotracer in thyroid in 56 patients compared to significantly higher uptake in thyroid nodules 32 . PSMA expression in neovasculature was observed in a wide spectrum of thyroid tumors from benign adenomas to highly-aggressive undifferentiated carcinomas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No cancer cells except one case of PDTC were immunoreactive for PSMA. No normal thyroid epithelium or non-neoplastic microvasculature were PSMA-positive, which is in the line with the recent biodistribution study that found minimal uptake of 68 Ga-PSMA-11 PET/CT radiotracer in thyroid in 56 patients compared to significantly higher uptake in thyroid nodules 32 . PSMA expression in neovasculature was observed in a wide spectrum of thyroid tumors from benign adenomas to highly-aggressive undifferentiated carcinomas.…”
Section: Discussionsupporting
confidence: 91%
“…Considering described diffuse pattern of radiotracer uptake and our findings, inflammatory origin could be a possible reason. Another biodistribution study of 68 Ga-PSMA found occasional nodal uptake in axillary lymph nodes 32 . PSMA tracer positivity in lymph nodes may present serious pitfall as a mimic of metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Overall, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) are higher for 68 Ga-PSMA PET. 7,8 The findings in our case were in keeping with persistent localised disease within the unresected seminal vesicles. Because the initial surgery was limited by anatomic distortion, biopsy of the suspicious area or re-resection was not possible.…”
supporting
confidence: 85%
“…Trotz des Namens wurde eine physiologische Expression dieses onkologischen Targets auch in anderen Organen (z. B. im proximalen Nierentubulus, im Duodenum und v. a. in den Kopfspeicheldrüsen [62]) als auch bei weiteren Tumorentitäten (u. a. Nierenzellkarzinom) und in der Neovaskularisierung verschiedenster Malignome nachgewiesen [63]. Die genaue Genese der Überexpression dieser Folathydrolase I oder Glutamatcarboxypeptidase II auf entdifferenzierten Prostatakarzinomzellen bleibt ungeklärt, die inzwischen sehr umfangreichen klinischen Resultate zeigen jedoch, dass es sich ideal zur Theranostik eignet [64,65].…”
Section: Psma-vermittelte Radioligandentherapieunclassified